Putting the “TEAM” back into virtual teams - Gilson, L.; Costa, P.; O’Neill, T. A.; Maynard, M. T. (Organizational Dynamics, 2021)
It is Monday morning and after a quick cup of coffee, you move from the kitchen to your home office and fire up your laptop. Today starts with a Zoom meeting with the accounting team to discuss last quarter’s earnings. After a quick friendly chat about everyone’s weekend and the challenges that Sarah faces with her 5-year old starting kindergarten and John’s teenager starting his college search, Mary shares her screen and the real work begins. The meeting ends with everyone listing out next steps, plans for the upcoming quarter, and confirming that they can meet at this same time next month. Fifteen minutes later, after a quick check of your email, you are in another meeting, this time with the communications team. Unlike the accounting team, which is comprised of individuals who are all located in the same city; the communications team’s members are located around the world and they use Microsoft Teams to communicate.